Deletion of bZIP Transcription Factor PratfA Reveals Specialized Metabolites Potentially Regulating Stress Response in Penicillium raistrickii - Anxin Zhang; Shu Zhang; Xinran Xu; Wen-Bing Yin (Journal of Fungi)
Fungal secondary metabolism (SM) is highly correlated with physiological processes that are typically regulated by pleiotropic regulators. In this study, we purposefully altered PratfA, a crucial regulator associated with oxidative stress in Penicillium raistrickii CGMCC 3.1066. After the knockout of PratfA, a novel polyketide (PK) raistrilide A (1) and the known nonribosomal peptide (NRP) tunicoidine (2) subsequently disappeared. Notably, compound 1 is a rare octaketone derivative and contains two unsubstituted cis-double bonds, demonstrating its unique biosynthetic mechanism. The knockout of PratfA resulted in the disappearance of 1–2 and greatly increased the susceptibility of ΔPratfA mutant strain to oxidative stress, rendering it nearly impossible to survive in such environments. At present, the OE⸬PratfA strain showed no phenotypic or oxidative stress sensitivity differences compared to the wild-type strain. Our findings highlight that the oxidative-stress-related transcription factor (TF) PratfA influences SM pathways in P. raistrickii. The manipulation of regulatory factors can guide the discovery of novel natural products (NPs).